ELEMEN STRATEGI UNTUK PERSAINGAN DAN BERKELANJUTANNYA MARINE SUPPORT INDUSTRY - Prayetno, Eko; Putra, Risandi D; Saputra, H; Deah, A; M, Mufti F (Fakultas Teknik Universitas Maritim Raja Ali Haji, 2016)
Marine industry is one of the element of great importance to a country, especially the State is a maritime country. Marine industry is neither an institution that can stand alone. This means that marine industry has a close relationship with the other industry that is support marine industry. In several developing countries, they have a way to keep the marine support industry can be competitive to face global challenges. Looking at this condition, there is a strong link between the marine support industry and the competitive element. To realize a marine support industry keep competitive and sustainable, marine support industry must have a competative element to the strategic criteria. The study will choose what elements of competitive strategy in order to support marine industry stay competative and sustainable. The competitive elements that generated in this report can be used by all maritime nations to maintain maritime support industry stay competitive and sustainable, such as state of Indonesia. Indonesia as a maritime country and has many islands and also has a vast sea  area must have a strong maritime industry to keep stay competitive and able to contribute in the global maritime industry.